Viscoelasticity Investigation of Semiconductor NP (CdS and PbS) Controlled Biomimetic Nanoparticle Hydrogels - Zhao, Dan; Zhang, Wang; Chen, Zhi-Zhou (Frontiers in Chemistry, 2022)
The viscoelastic properties of colloidal nanoparticles (NPs) make it opportunities to construct novel compounds in many different fields. The interparticle forces of inorganic particles on colloidal NPs are important for forming a mechanically stable particulate network espcially the NP-based soft matter in the self-assembly process. Here, by capped with the same surface ligand L-Glutathione (GSH), two semiconductor NPs (CdS and PbS) controlled biomimetic nanoparticle hydrogels were obtained, namely CdS@GSH and PbS@GSH. Dependence of viscoelastic properties of the colloidal suspensions on nanoparticles sizes, concentrations, and pH has been carried out.The results show that viscoelastic properties of CdS@GSH are stronger than PbS@GSH because of stronger surface bonding ability of inorganic particles and GSH. The hydrogels made from the smallest nanoparticles display the highest stiffness, which was attributed to the drastic change of GSH configurations. Unlike CdS@GSH hydrogel system, the changes of NPs concentrations and pH value had great influence on PbS@GSH hydrogel system. The higher the proportion of water in the small particle size PbS@GSH hydrogel system, the greater the mechanical properties. The stronger the alkalinity in the large particle size PbS@GSH hydrogel system, the greater the hardness and storage modulus. Solution˗state nuclear magnetic resonance (NMR) uncovered that the ligand GSH forms surface layers with different thickness varying from different coordination mode which is induced by different semiconductor NPs. Moreover, increasing the pH value of the PbS@GSH hydrogel system will dissociate the surface GSH molecules to form Pb2+ and GSH complexes which could enhance the viscoelastic properties.